The Role of Correctional Institutions In Empowering Prisoners For The Character of Prisoners - Batubara, Falan; Manullang, Herlina; Esther, July (Indonesian Journal of Law and Justice, 2024)
The purpose of this study is to explore the role of correctional institutions in shaping the character of prisoners. The concept of inmate development in correctional institutions is analyzed and a normative juridical approach is used to review and analyze laws and regulations related to the concept of inmate development in shaping their character. The results showed that there are still various obstacles to the successful implementation of an activity, the large number of prisoners makes the correctional institution over capacity where the capacity as of December 2023 should only be 1,200 people but there are 1,280 people in it so that there is an overcapacity of 6% things like this are the obstacles most often encountered against the success of empowerment in correctional institutions, besides that several obstacles are encountered to maximize coaching. The lack of budget in the process of fostering Wargabinaan often hinders the implementation of the coaching program, which causes prison officers to prepare funding efforts that can help the implementation by forming cooperatives among fellow prison officers, however, even that has not been able to meet the financing to the maximum so that the purpose of coaching is not maximally achieved. In an effort to empower prisoners, prison officers maximize prison officers in fostering prison officers with the aim that after the prisoner comes out / finishes serving his sentence, he can re-interact with the community.